2015
DOI: 10.1155/2015/180526
|View full text |Cite
|
Sign up to set email alerts
|

Hyperhemolysis Syndrome without Underlying Hematologic Disease

Abstract: Introduction. Hyperhemolysis is characterized by a life-threatening hemolytic transfusion reaction, with hemoglobin (Hb) and hematocrit (Hct) dropping markedly lower than before transfusion. This phenomenon, commonly described in sickle cell disease, is a rare occurrence in patients without hemoglobinopathies. Case Report. A 55-year-old male presented to the hospital after a motorcycle crash and received 10 units of cross-matched blood for active bleeding. The patient was blood group O, with a negative antibod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 21 publications
2
19
0
Order By: Relevance
“…Eberly et al [3] recently reported a case with hyperhemolysis without hematologic disease, that her laboratory tests results were as the same as our patient results. IVIG and steroids [8], avoiding further blood transfusion [9], plasma-to-RBC replacement [11] are different treatment of the HS.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…Eberly et al [3] recently reported a case with hyperhemolysis without hematologic disease, that her laboratory tests results were as the same as our patient results. IVIG and steroids [8], avoiding further blood transfusion [9], plasma-to-RBC replacement [11] are different treatment of the HS.…”
Section: Discussionsupporting
confidence: 87%
“…Santos et al [5] described two acute (with negative DAT) and chronic (with positive DAT) forms of HS. Transfusions in a hyperhemolytic episode are able to accelerate hemolysis [3], which was seen in our case. Jka negative blood product (compatible blood) could not increase Hb level in our patient, and his positive auto control result directed that autologous RBC destruction may occur.…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations